Critical Analysis of the Use of Arabic Language by Contemporary Critics of the Prophetic Sunnah in Modern Times - Ali Mustafa, Ali Salih (Journal of Islamic and Religious Studies, 2024)
Many modern critics of the Prophetic Sunnah have used Arabic linguistic sciences to argue that numerous authentic Hadiths contain interpolations and misunderstandings introduced by narrators. They assert that these Hadiths cannot be reliably attributed to the Prophet Muhammad (peace be upon him) despite their inclusion in the most authoritative collections of Sahih al-Bukhari and Sahih Muslim. Critics analyze particles' meanings, lexical definitions, semantic levels, and contextual factors to demonstrate inconsistencies with Arabic linguistic norms and the Prophet's eloquence. This study highlights instances where contemporary critics demonstrate their grasp of linguistic vocabulary and ability to apply Arabic rules and styles in textual interpretation and critique. Employing an analytical approach, the study scrutinizes critics' arguments by interpreting their critiques of Hadith texts and deconstructing their assertions to understand their objections' basis and theoretical framework. Evaluating these criticisms against Arabic linguistic principles distinguishes valid points from invalid ones, critiqued within the framework of scientific research criteria. Ultimately, the study finds that critics often rely on limited linguistic knowledge, leading to flawed interpretations and critiques contradicting the Arabic language principles they claim to uphold in rejecting authentic Hadiths.